Quality of Life of Diabetic Patients Type -2- in Urban and Rural Areas in Kirkuk City (Comparative Study - Abid Salih Kumait (College of Nursing,University of Mosul, 2014)
Background and Objectives: Diabetes mellitus has become representing one of the most challenging public health problems of the 21st century. It is a metabolic disease characterized by high blood glucose levels (hyperglycemia) which may arise from defects in the secretion of insulin, defects in insulin action, or both. Diabetic patients suffering from worse quality of life in rural and urban area. Aims of the study were to assess quality of life Type-2- of diabetic patients in rural and urban area , to identify the relationship between some characteristics of diabetic patients and quality of life and comparison of quality of life of diabetic patients between urban and rural area in Kirkuk city. Material and Method: The non- experimental approach and descriptive design was used in this study . The study was conducted at Azadi Teaching Hospital in Kirkuk city and Al-Hawija General Hospital at Al- Hawija district during the period from 15th November 2012 to the 20th of June 2013 .Purposive sample consists of (110) clients from urban area who visited Azadi Teaching Hospital and (110) clients from rural area who visited Al-Hawija General Hospital . In order to collect the study information, a questionnaire was constructed depending on the criteria of World Health Organization scale (WHO ) format that modified by researcher and related literature. It composed of two parts , part one included ( 5 ) items which focused on the client demographic characteristics such as (age, gender, marital status, residence , occupation , level of education .Diabetes Mellitus Quality of life questionnaire is the instrument that consists of (5) domains. The domains are Independence , daily physical activities , Psycho-social , beliefs , environmental and circumstances. The overall questions includes (80 ) items. The questions were rated on (3) point- likert scale. The score ranges between (0-240), never ( 1), sometimes (2), always (3).content validity was determined by presenting the questionnaire to a panel of (10 ) experts. Results: The data analysis shows that most of the type -2- diabetic patients were male in urban and rural area and constituted (75.3% ) and ( 61.8 % ) respectively . In relation to the age , high percentage of the sample were between age (55-64 ) years in urban and rural area and constituted (32.7% ) and (34.5 % ) respectively .Also the data analysis showed that there is a significant statistical association between health related quality of life (HRQoL) items that are related to independency, daily physical activities, psychosocial aspects ,beliefs and environmental circumstances. Also the study concluded that health problems of diabetic patients related to quality of life differs in sub domains have mild effects on the quality of life of patients with diabetic in rural than urban area . Conclusions: The socio demographic characteristic of quality of life of type 2- diabetic clients (age, gender, marital status, level of education, jobs ) are different in effects on independency, daily physical activities, psycho-social aspects, beliefs and environment Quality of life of diabetic patients type -2- more impact in rural than urban area. Key words: Quality of Life, Diabetic Patients Type -2-, Urban, Rural